Do exposure to outdoor temperatures, NO2 and PM10 affect the work-related injuries risk? A case-crossover study in three Italian cities, 2001–2010. Issue 8 (18th August 2019) - Schifano, Patrizia; Asta, Federica; Marinaccio, Alessandro; Bonafede, Michela; Davoli, Marina; Michelozzi, Paola
Abstract : Objectives: Studies on the effect of temperature on rates of work-related injuries (WRIs) are very recent, and are evolving in depth and scope. However, less is known about potential effects of air pollutants. Our objective was to analyse the association between WRI and NO2, PM10 and air temperature in three major Italian cities, and to identify groups of workers more at risk in Italy. Design: Time-stratified case-crossover study. Settings: Milan, Turin, Rome, years 2001–2010. Participants: A total of 468 816 WRI occurred between 2001 and 2010 in Milan, Turin and Rome were extracted from the Italian national workers' compensation authority database. Main outcomes: Associations between WRI and temperature, PM10, NO2, separately in the warm and in the cold season (WS, May–September; CS, November–February). Effect modification was studied by economic sector, occupational activity and indoor/outdoor job activity. Results: Exposure to NO2 (lag 0–8) showed the highest effect on the risk of WRI, with ORs ranging from 1.20 (95% CI 1.16 to 1.24) in Milan to 1.30 (95% CI 1.24 to 1.37) in Turin in the WS. The effect of exposure to PM10 was milder but consistent across all cities: ORs from 1.09 (95% CI 1.05 to 1.12) in Turin to 1.15 (95% CI 1.11 to 1.18) in Rome. Temperature was associated with risk of WRI only among those working in construction (highest association in Rome 1.06; 95% CI 1.01 to 1.12), transportation (highest association in Milan 1.05; 95% CI 0.96 to 1.14) and the energy industry (highest association in Milan 1.57; 95% CI 1.03 to 2.38) in the WS in all cities. A weak effect of low temperatures was observed in the CS only in Rome. Conclusions: Exposures to NO2 resulted as strongest hazard for WRIs, mainly in warm months, while the independent effect of temperature was significant only in specific subgroups of workers. These results could be considered to better plan safety prevention programmes.